REKONTRUKSI PEMAHAMAN HADIS TENTANG LARANGAN DAN KEBOLEHAN MEMINTA RUQYAH DALAM PERSPEKTIF SOSIO-HISTORIS - Tubagus Eling Kinayungan; Mohammad Syifa Amin Widigdo (EL-ADABI : Jurnal Studi Islam, 2025)
Debates surrounding the practice of ruqyah as a healing method remain a dynamic discourse within Muslim societies. These differing views largely stem from textual interpretations of the Prophet’s hadiths, particularly those concerning the prohibition and permissibility of ruqyah. Some groups adopt a highly cautious stance by discouraging requests for ruqyah, while others regard it as a necessary form of spiritual effort in seeking healing. This study aims to analyze the authenticity of hadiths related to ruqyah and to examine their socio-historical context in order to achieve a comprehensive and balanced understanding. This research employs a descriptive–explanatory approach using library research methods. The primary data consist of hadiths on ruqyah, which are analyzed through hadith criticism and interpreted by considering the socio-cultural background of pre-Islamic Arabian society and the prophetic era. The findings indicate that the prohibition of ruqyah in certain hadiths refers specifically to incantations containing elements of polytheism, as practiced in pre-Islamic shamanistic traditions. Conversely, ruqyah that is free from polytheistic elements, utilizes verses of the Qur’an, and consists of supplications directed solely to Allah is deemed permissible. Thus, the Prophet Muhammad (peace be upon him) did not abolish the practice of ruqyah, but rather reformed and reoriented it in accordance with the principle of tawḥīd. These findings underscore the importance of a socio-historical approach in understanding hadiths on ruqyah in a contextual and applicable manner.